Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1093/jn/132.8.2241
|View full text |Cite
|
Sign up to set email alerts
|

Saponins from Platycodi Radix Ameliorate High Fat Diet–Induced Obesity in Mice

Abstract: We examined the effects of crude saponins isolated from Platycodi radix on the degree on fat storage induced in mice by feeding a high fat diet for 9 wk. We reported previously that feeding mice a high fat diet for a longer time caused obesity and fatty liver compared with those fed a low fat diet, nonpurified diet. Feeding a high fat diet containing 10 or 30 g/kg crude saponins prevented the body and parametrial adipose tissue weight increases and hepatic steatosis of mice fed the high fat diet alone. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
144
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(160 citation statements)
references
References 14 publications
6
144
2
4
Order By: Relevance
“…The animal experiment showed that the body weight reduction was highly linked with the calorie intake restriction, which is obviously inconsistent with the previous reports. 1,2 We also observed that a cholesterollowering effect was mainly attributed by the reduction of LDL-cholesterol. A beneficial alteration in the hepatic tissues and fecal excretion was also noted.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…The animal experiment showed that the body weight reduction was highly linked with the calorie intake restriction, which is obviously inconsistent with the previous reports. 1,2 We also observed that a cholesterollowering effect was mainly attributed by the reduction of LDL-cholesterol. A beneficial alteration in the hepatic tissues and fecal excretion was also noted.…”
Section: Introductionmentioning
confidence: 77%
“…Two essential factors are noted here: one is the suppression of the food intake with high correlation to the body weight loss; the other is the regulation of the cholesterol metabolism with the resultant improvement of the lipoprotein composition and the hepatic lipid-lowering effect. Undoubtedly, PS is more deeply involved in lipid metabolism regulation than was previously understood, 2 and represents a promising candidate in the treatment of the obesity and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations